Examining student learning outcomes on the topic of invertebrates through problem-based learning - Zannah, Nur Lailil; Damopolii, Insar; Iwan, Iwan; Rahman, Sari Rahayu (Inornatus: Biology Education Journal, 2018)
The research aims to examine the effect of treatment with the application of problem-based learning (PBL) on learning outcomes of student. The topic of teaching biology in this research is invertebrate material. During the conduct of this research, a quasi-experimental non-equivalent control group program was done. A total of 45 students who were divided into two classes (control = 20 students, experiment = 25 students) were taken randomly from a total of eight classes. The instrument for measuring student learning outcomes is seven items and has been validated by experts and empirically. The t test was used to compare data. The results of the research show that there is no difference in learning outcomes in the two classes (experimental and control) with sig. 0.825. This research concludes that problem-based learning has no impact on student learning outcomes on invertebrate material. The future research recommendation is to provide innovation in problem-based learning to increase its effectiveness on student performance.